Professor de séries iniciais do ensino fundamental em escolas públicas estaduais de São Paulo: posições sociais e condições de vida e trabalho - Penna, Marieta Gouvêa de Oliveira (2007)
The theme of this research is the teachers educational exercise from the early education of elementary school in public schools of the state of São Paulo, from a sociological perspective. Based on Pierre Bourdieu s theory of the action, the teaching profession is understood as a social function, with the objective of analyzing the material conditions which the teachers are submitted to and their position in the space of the social relationships. For this reason, aspects related to the teachers social origin, trajectory and class belonging are analyzed, with the intention of detecting facets of the agents family habitus who have been dedicating themselves to the exercise of that function. We also analyze aspects of the conditions of the teachers work; of the cultural capital; of the relationships they establish with the knowledge in the exercise of the function; as well as of the practices accomplished by them which were explicited in their depositions, that constitute and are constituted by facets of the habitus related to the teaching profession in that part of the educational instruction that express the school culture historically instituted. Interviews were accomplished with ten teachers, two parents, four students, one coordinator and one principal; over questionnaires with 16 teachers. The research data evidenced that, for their origin, the majority of the teachers belong to the popular classes, but the educational exercise represented possibility of social ascension, positioning them in the middle classes. It was possible to realize existent regularities in the teachers' family habitus, concerning the valorization of the work and the educational instruction as strategy of social ascension, besides the submission of the women to the masculine universe, which join the practices accomplished by the teachers in the school, at the same time expressed in them. We could also verify the conditions of the teachers work related to the space of the social relationships, leading them to establish distinction strategies in relation to their students and the students family, expressed in their view of the world. The practices accomplished by the teachers and informed in their depositions were centered in the moralization and the children s training, expressing aspects of the school culture and the habitus related to the exercise of that function. We can stand out that the educational exercise, even being socially depreciated, facilitates the teachers to establish distinction strategies and bargain symbolic capital, besides meaning improvements in their life conditions in terms of cultural and economic capital